Aberrant cellular immune responses in humans infected persistently with parvovirus B19. - Isa, A; Norbeck, O; Hirbod, T; Lundqvist, A; Kasprowicz, V; Bowness, P; Klenerman, P; Broliden, K; Tolfvenstam, T (2006)
A subset of parvovirus B19 (B19) infected patients retains the infection for years, as defined by detection of B19 DNA in bone marrow. Thus far, analysis of B19-specific humoral immune responses and viral genome variations has not revealed a mechanism for the absent viral clearance. In this study, ex-vivo cellular immune responses were assessed by enzyme linked immunospot assay mounted against the majority of the translated viral genome. Compared to seropositive healthy individuals, individuals with B19 persistence (2-8 years) showed larger number of responses to the structural proteins (P = 0.0022), whereas responses to the non-structural protein were of lower magnitude (P = 0.012). These observations provide the first findings of immunological discrepancies between individuals with B19 persistence and healthy individuals, findings that may reflect both failed immunity and antigenic exhaustion.